2019
DOI: 10.3846/jbem.2019.8339
|View full text |Cite
|
Sign up to set email alerts
|

Managing Human Resources in Nursing: The Relationship of Nurses’ Working Time and Patients’ Independence Level

Abstract: A skilled, competent, and motivated nursing workforce is crucial for a well-functioning health care system. Nurses’ professional activities done on a regular basis, their workload, and occupancy are related to the patient’s health status, dependence level and care needs. Therefore, managing human resources in nursing by effectively distributing nurses’ working time and monitoring their workload for safe and high quality care, managers should rely on the severity of patients’ health status and their independenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 35 publications
0
12
0
8
Order By: Relevance
“…In the reaction to current trends, companies are forced to innovate their processes in order to retain their employees or there is the threat of employees leaving to competitor and potential survival of a company can be endangered (Nouri & Mousavi, 2020;Pham et al, 2019;Kampf et al, 2018). Within this context it is necessary to motivate employees because researches that dealt with employee motivation (Azis et al, 2019;Čiarnienė et al, 2019;Mulyani et al, 2019) focus on the fact that motivated employees will look at the tasks better way, quality oriented and will work more effectively and with higher productivity. Effective motivation will consequently reflect in reaching good work results.…”
Section: Discussionmentioning
confidence: 99%
“…In the reaction to current trends, companies are forced to innovate their processes in order to retain their employees or there is the threat of employees leaving to competitor and potential survival of a company can be endangered (Nouri & Mousavi, 2020;Pham et al, 2019;Kampf et al, 2018). Within this context it is necessary to motivate employees because researches that dealt with employee motivation (Azis et al, 2019;Čiarnienė et al, 2019;Mulyani et al, 2019) focus on the fact that motivated employees will look at the tasks better way, quality oriented and will work more effectively and with higher productivity. Effective motivation will consequently reflect in reaching good work results.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the complex work of nurses, to determine the patients' nursing needs and to estimate precisely the nurses' workload, various classifications and methodologies have been developed and tested during the last decades (Fasoli & Haddock, 2010;Webster et al, 2011). However, precise balancing of the nurse-patient ratio is extremely difficult due to the level of nurses' competence and motivation, specific fluent characteristics of nursing activities, the number of patients and the severity of their state, their self-sufficiency as well as other specific organisational features of nursing care in a unit (Carmona-Monge et al, 2013;Čiarnienė et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Also, workload management in nursing services requires systems to classify patients according to their needs and health conditions to structure a compassionate care plan, where the level of dependence of the patient (Čiarnienė et al, 2019; Vandresen et al, 2018) and the mental health state (Nilsson et al, 2016) is explicitly considered factors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are coherent with those described by Carvajal Carrascal et al (2016) in similar health institutions, in which they concluded that it is necessary to improve the working environment, as a factor that promotes the quality of care and satisfaction of the stakeholders. Also, workload management in nursing services requires systems to classify patients according to their needs and health conditions to structure a compassionate care plan, where the level of dependence of the patient (Čiarniene . et al, 2019;Vandresen et al, 2018) and the mental health state (Nilsson et al, 2016) is explicitly considered factors.…”
Section: Marked With "•"mentioning
confidence: 99%